Epstein-Barr Virus in Nasopharyngeal Carcinoma: Molecular Mechanisms and Oncogenic Drivers - Mohd Aminudin, Mustapha; Sai Peng, Sim (Japan University of Health Sciences & Japan International Cultural Exchange Foundation (JICEF), 2025)
Background: Nasopharyngeal carcinoma (NPC) is a malignancy strongly associated with Epstein-Barr virus (EBV) infection. EBV is detected in nearly all non-keratinizing NPC cases and plays a central role in tumor initiation, progression, and immune evasion. Objective: To review the key molecular mechanisms by which EBV contributes to NPC development, with a focus on viral oncogenes, host-pathogen interactions, and potential therapeutic implications. Method: A literature-based review of current evidence from molecular oncology, virology, and NPC-focused clinical studies was conducted to outline EBV-driven oncogenic pathways and their role in NPC. Conclusion: Understanding EBV-driven molecular mechanisms in NPC provides critical insights into the disease's etiology and highlights novel opportunities for early diagnosis, prognostic biomarker development, and targeted therapy.